Impact of ethanol, methyl tert-butyl ether and a gasoline–ethanol blend on the performance characteristics and hydrocarbon emissions of an opposed-piston engine. Issue 2 (17th February 2020) - Yontar, Ahmet Alper
Abstract: A prototype opposed-piston engine was tested with gasoline, ethanol, methyl tert-butyl ether (MTBE) and a gasoline–ethanol blend (E85) at full load. This is the first test of an opposed-piston engine considering engine speed, lambda, compression ratio and injection timing parameters, and comparing four fuels for the same engine. Results show that the torque for E85 is higher than for gasoline by about 3.34%. The brake specific fuel consumption (BSFC) for E85 is 30.63% higher than that of MTBE at the minimum BSFC point. The brake thermal efficiency for E85 and ethanol are overall 9.56% and 10.27% higher, respectively, than that of gasoline. At maximum torque speed, the lambda effect tests show the power for gasoline is approximately 3.26% lower than that of ethanol. The unburned fuel emission for gasoline is overall 51.51% lower than for ethanol. The compression ratio effect results show that the torque for gasoline is overall 3.03% and 1.97% less than for MTBE and E85, respectively. The hydrocarbon (HC) emission for gasoline is overall 4.94% and 3.53% higher than for ethanol and E85. The highest brake mean effective pressure areas were observed with ethanol, and the maps show high levels of HC in ethanol and E85.